Assessing birth experience in fathers as an important aspect of clinical obstetrics: how applicable is Salmon׳s Item List for men? - Wallwiener, Stephanie; Hoffmann, Lutz; Dienes, Aimée (Midwifery, 2015)
Objective - validated questionnaire assessment of fathers׳ experiences during childbirth is lacking in routine clinical practice. Salmon׳s Item List is a short, validated method used for the assessment of birth experience in mothers in both English- and German-speaking communities. With little to no validated data available for fathers, this pilot study aimed to assess the applicability of the German version of Salmon׳s Item List, including a multidimensional birth experience concept, in fathers. - Design - longitudinal study. Data were collected by questionnaires. - Setting - University hospital in Germany. - Participants - the birth experiences of 102 fathers were assessed four to six weeks post partum using the German version of Salmon׳s Item List. - Measurements - construct validity testing with exploratory factor analysis using principal component analysis with varimax rotation was performed to identify the dimensions of childbirth experiences. Internal consistency was also analysed. - Findings - factor analysis yielded a four-factor solution comprising 17 items that accounted for 54.5% of the variance. The main domain was ‘fulfilment’, and the secondary domains were ‘emotional distress’, ‘physical discomfort’ and ‘emotional adaption’. For fulfilment, Cronbach׳s α met conventional reliability standards (0.87). - Key conclusions - Salmon׳s Item List is an appropriate instrument to assess birth experience in fathers in terms of fulfilment. Larger samples need to be examined in order to prove the stability of the factor structure before this can be extended to routine clinical assessment. - Implications for practice - a reduced version of Salmon׳s Item List may be useful as a screening tool for general assessment.
Available online 6 September 2014
Gesehen am 28.07.2020